Central Asian security : the new international context - Allison, Roy; Jonson, Lena, 1948- (Royal Institute of International Affairs ; Brookings Institution Press, 2001)
"The authors in this study assess internal security policy problems and examine the security content of evolving relations between the Central Asian states and regional and international powers - specifically the stakes, interests, and policies of Russia, China, Iran, Turkey, and the United States. While new possibilities for regional security cooperation in Central Asia can be explored, there remains a danger of destabilizing rivalry, which would fracture the region and hamper economic development. These dilemmas are examined by a team of specialists from Western Europe, the United States, Russia, and China."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved